Analysis of Borrelia burgdorferi Surface Proteins as Determinants in Establishing Host Cell Interactions - Schmit, Virginia L.; Patton, Toni G.; Gilmore, Robert D. (Frontiers in Microbiology, 2011)
Borrelia burgdorferi infection causes Lyme borreliosis in humans, a condition which can involve a systemic spread of the organism to colonize various tissues and organs. If the infection is left untreated by antimicrobials, it can lead to manifestations including, arthritis, carditis, and/or neurological problems. Identification and characterization of B. burgdorferi outer membrane proteins that facilitate cellular attachment and invasion to establish infection continue to be investigated. In this study, we sought to further define putative cell binding properties of surface-exposed B. burgdorferi proteins by observing whether cellular adherence could be blocked by antibodies. B. burgdorferi mixed separately with monoclonal antibodies against outer surface protein (Osp) A, OspC, decorin-binding protein (Dbp) A, BBA64, and RevA antigens were incubated with human umbilical vein endothelial cells (HUVEC) and human neuroglial cells (H4). B. burgdorferi treated with anti-OspA, -DbpA, and –BBA64 monoclonal antibodies showed a significant decrease in cellular association compared to controls, whereas B. burgdorferi treated with anti-OspC and anti-RevA showed no reduction in cellular attachment. Additionally, temporal transcriptional analyses revealed upregulated expression of bba64, ospA, and dbpA during coincubation with cells. Together, the data provide evidence that OspA, DbpA, and BBA64 function in host cell adherence and infection mechanisms.